Blue Electroluminescence: Blue Electrofluorescence Resulting from Exergonic Harvesting of Triplet Excitons (Advanced Optical Materials 18/2019). Issue 18 (18th September 2019) - Yi, Seung Yeon; Ihn, Soo‐Ghang; Sim, Myungsun; Kim, Jong Soo; Kim, Inkoo; Chung, Yeon Sook; Huh, Dal Ho; Kim, Sunghan; You, Youngmin
Abstract : Organic molecules capable of exciton harvest have been developed by Sunghan Kim, Youngmin You and co‐workers (see article number1900630 ). Exploiting the non‐bonding orbital enables exergonic conversion of triplet excitons into singlet excitons. The harvested singlet excitons produce efficient and medium‐tolerant blue fluorescence emission, without delayed emission components. The strategy can serve as a promising alternative to the existing principles for electroluminescence, because it permits rapid harvesting of triplet exciton, thereby avoiding any hazardous annihilation processes.